Cancer statistics for American Indian and Alaska Native individuals, 2022: Including increasing disparities in early onset colorectal cancer. (8th November 2022) - Kratzer, Tyler B.; Jemal, Ahmedin; Miller, Kimberly D.; Nash, Sarah; Wiggins, Charles; Redwood, Diana; Smith, Robert; Siegel, Rebecca L.
Abstract: American Indian and Alaska Native (AIAN) individuals are diverse culturally and geographically but share a high prevalence of chronic illness, largely because of obstacles to high‐quality health care. The authors comprehensively examined cancer incidence and mortality among non‐Hispanic AIAN individuals, compared with non‐Hispanic White individuals for context, using population‐based data from the National Cancer Institute, the Centers for Disease Control and Prevention, and the North American Association of Central Cancer Registries. Overall cancer rates among AIAN individuals were 2% higher than among White individuals for incidence (2014 through 2018, confined to Purchased/Referred Care Delivery Area counties to reduce racial misclassification) but 18% higher for mortality (2015 through 2019). However, disparities varied widely by cancer type and geographic region. For example, breast and prostate cancer mortality rates are 8% and 31% higher, respectively, in AIAN individuals than in White individuals despite lower incidence and the availability of early detection tests for these cancers. The burden among AIAN individuals is highest for infection‐related cancers (liver, stomach, and cervix), for kidney cancer, and for colorectal cancer among indigenous Alaskans (91.3 vs. 35.5 cases per 100, 000 for White Alaskans), who have the highest rates in the world. Steep increases for early onset colorectal cancer, from 18.8 cases per 100, 000 Native Alaskans aged 20–49 years during 1998 through 2002 to 34.8 cases per 100, 000 during 2014 through 2018, exacerbated this disparity. Death rates for infection‐related cancers (liver, stomach, and cervix), as well as kidney cancer, were approximately two‐fold higher among AIAN individuals compared with White individuals. These findings highlight the need for more effective strategies to reduce the prevalence of chronic oncogenic infections and improve access to high‐quality cancer screening and treatment for AIAN individuals. Mitigating the disparate burden will require expanded financial support of tribal health care as well as increased collaboration and engagement with this marginalized population.